The effects of using language games on Vietnamese young learners' efl vocabulary retention at Phuong Thanh C primary School in Tra Vinh province - Phạm Thị Mỹ Hạnh (Trường Đại học Trà Vinh, 2019)
Although there are many studies to examine the effects of language games on speaking, writing, listening and grammar, in Vietnam few studies have investigated the effect of language games on young learners’ vocabulary retention, especially in the researcher’s school. Therefore, the study is conducted to: Investigate the effects of using language games on Vietnamese young learners’ EFL vocabulary retention at Phuong Thanh C primary school;